Activated carbon/titanium dioxide composite to adsorb volatile organic compounds associated with human body odor. Issue 11 (November 2020) - Hara, Takeshi; Nabei, Haruna; Kyuka, Ayumi
Abstract: The human body generates various malodor compounds in different body parts and even in the same parts. A more effective and versatile deodorant material that can suppress various key contributors to the body odor must be developed to improve the quality of life of affected individuals. In this study, activated carbon (AC) was found to have higher adsorption ability toward key body odor-generating compounds than zinc oxide (ZnO), which is a well-known deodorant material. To prevent pigmentation of human skin induced by the direct application of AC, white activated carbon (WAC) was developed by blending AC, titanium dioxide (TiO2 ), and ammonium acrylate copolymer. AC to TiO2 ratio of 1:6 was found to be the optimum blending ratio to form WAC. Compared with ZnO, this optimal WAC exhibited higher adsorption ability toward five key body odor compounds. The in vivo evaluation of the sample containing WAC revealed that it significantly suppressed the generation of axillary odor without a bactericidal effect. The developed WAC can effectively suppress the human body odor in different body parts. These findings are valuable for individuals experiencing psychological stress attributed to their unpleasant body odor. Abstract : Materials Science; Analytical Chemistry; Pharmaceutical Science; Body odor; Axillary odor; Activated carbon; Adsorption; Deodorant